Sine of Summations!

Algebra Level 4

k = 1 sin 1 ( k k 1 k ( k + 1 ) ) = θ \large \sum _{ k=1 }^{ \infty }{ \sin ^{ -1 }{ \left( \frac { \sqrt { k } - \sqrt { k - 1 } }{ \sqrt { k( k + 1) } } \right) } } = \theta

Find sin θ \sin \theta .


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Feb 14, 2018

Since k ( k + 1 ) ( k k 1 ) 2 = k 2 k + 1 + 2 k ( k 1 ) = ( k ( k 1 ) + 1 ) 2 k(k+1) - (\sqrt{k} - \sqrt{k-1})^2 \; = \; k^2 - k + 1 + 2\sqrt{k(k-1)} \; = \; \big(\sqrt{k(k-1)} + 1\big)^2 we deduce that sin 1 ( k k 1 k ( k + 1 ) ) = tan 1 ( k k 1 1 + k ( k 1 ) ) = tan 1 k tan 1 k 1 \sin^{-1}\left(\frac{\sqrt{k} - \sqrt{k-1}}{\sqrt{k(k+1)}}\right) \; = \; \tan^{-1}\left(\frac{\sqrt{k} - \sqrt{k-1}}{1 + \sqrt{k(k-1)}}\right) \; = \; \tan^{-1}\sqrt{k} - \tan^{-1}\sqrt{k-1} and hence the series telescopes, with θ = k = 1 ( tan 1 k tan 1 k 1 ) = 1 2 π \theta \; = \; \sum_{k=1}^\infty \big(\tan^{-1}\sqrt{k} - \tan^{-1}\sqrt{k-1}\big) \; = \; \tfrac12\pi which makes the answer 1 \boxed{1} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...